4CPS-231 Pharmacists in emergency departments – post-study workforce impact evaluation. (March 2019) - Huynh, C; Terry, D; Aiello, M; Whyte, SA; Hughes, E
Abstract : Background: The large Pharmacists in Emergency Departments (PIED) study published in 2017 1 –49 sites, 18 613 patients – demonstrated the potential for advanced clinical practice-trained pharmacist clinicians to manage patients attending the Emergency Departments (ED). It is not known how the hospital sites involved in PIED have responded in terms of workforce changes – for example if the study findings have resulted in a change in the workforce. This present study demonstrates for the first time the impact of the PIED study on the pharmacy workforce and, in particular, within the ED. Purpose: To evaluate the actual or potential changes in the roles of pharmacists working in the ED, post cross-sectional study evaluating roles of pharmacists, drivers and barriers. Material and methods: Fifty hospital sites were sent a 10-point survey by email to pharmacy leaders asking questions in relation to their workforce pre-, peri- and post-PIED study. The instrument measured the past (last 3 years), present (May 2018) and future provision of pharmacy services to the ED. This included the number of whole time equivalent (WTE) pharmacists working in the ED. Results: Seventeen responses were received, representing 15/50 hospital sites (28%). In the past, 7/15 sites had pharmacy resources with at least 0.8 WTE pharmacists ranging from band 7–8b. In terms of the resources 5/7 sites had temporary roles that were non-substantive. In terms of present resources, 8/15 sites had resources, ranging from 0.1 (unfunded) to 1 WTE (funded). None of the hospitals provided 7 day per week cover. Regarding the future, 11/17 sites had plans in place to propose increased pharmacy resources within the ED – all commented on issues in relation to funding and securing substantive posts for ED-based pharmacists. Conclusion: Despite published evidence concerning the potential benefits of having advanced trained pharmacists managing ED cases, the sites that responded to this survey show that there are barriers regarding funding and stakeholders agreeing to substantive posts being established. References and/or acknowledgements: 1. Hughes E, Terry D, Huynh C, et al. Future enhanced clinical role of pharmacists in Emergency Departments in England: multi-site observational evaluation. Int J Clin Pharm2017;39:960–8. No conflict of interest.